O-012 Long term angiographic follow-up of aneurysms treated with self-expandable stents. (4th July 2012) - Nishido, H; Piotin, M; Bartolini, B; Pistocchi, S; Redjem, H; Blanc, R
Abstract : Purpose: Stent-assisted coiling of intracranial aneurysms has proved to promote aneurysm occlusion and to reduce aneurysm recurrence. First reports were promising but longer follow-up are needed to confirm the benefits of stenting over coiling without stents. Materials and Methods: Over the last 9 years, we treated selectively with coils 1621 aneurysms; 320 (including 38 in the setting of SAH) with stent-assistance, 1321 (628 in the setting of SAH) with coiling without stent-assistance, in 1253 patients. A retrospective review was conducted on patients that were followed at least for 18 months after endovascular treatment. Categorization was based on presence and type of stent assistance (none, single, X and Y-stenting). The rates of angiographic recanalization, rehemorrhage, and retreatment were analyzed. Results: 493 aneurysms were treated with coil embolization and 95 aneurysms with stent-assisted coiling (87 single-stent, 6 Y-stent, 2 X-stent). Mean angiographic follow-up was 34 months for stent-assisted coiled aneurysms, 38 months for coiled aneurysms (p=0.0542). Stent-assisted coiled aneurysms were larger (mean 7.7 mm) than coiled aneurysms (mean 6.6 mm) (p=0.0195). Stented aneurysms had significantly lower recanalization (12.6% vs 35.7%, p<0.0001). Retreatment rate was lower in the stented group (4.2%) (4/95) vs 8.9% (44/493) in the non-stented aneurysms (p=0.1527). Rehemorrhage occurred in two patients in the coiled group, whereas none were noted in the stented group (p=1). In multivariate analysis, larger aneurysms, non-stented aneurysms, and SAH at presentation were predictors of aneurysm recanalization. Conclusion: Long-term follow-up demonstrate that stent-assisted coiled aneurysms have lower recurrence, retreatment, and rehemorrhage rates than aneurysms coiled without stent assistance. Competing interests: None.